Psychological and Social Satisfaction among University Students - Taha, Aslam Hussam; Mohamed, Annam Hasany (Journal of Tikrit University for Humanities, 2025)
Psychological satisfaction is one of the most significant challenges faced by university students. Individuals who struggle to fulfill their needs in a constructive manner may resort to illegal methods and techniques to achieve a sense of compatibility. Therefore, this research aims to explore and support university students in consolidating the concepts of personal development while fostering their psychological and social well-being. The current research aims to eliminate negative perceptions that contribute to an individual’s feelings of psychological and social dissatisfaction. It highlights the most effective methods and techniques that students can employ to enhance their psychological and social well-being. Additionally, the study seeks to establish a future vision that outlines guidelines, principles, and strategies for improving psychological and social satisfaction among university students. After conducting thorough research and investigating relevant facts, as well as reviewing theories, literature, and studies related to the current topic, it became evident that an individual’s psychological satisfaction is influenced by several factors, including: Respect: Al-Shammari’s study (2003) and other research indicate that as we enhance respect for students, their psychological and social satisfaction increases. The study conducted by Al-Douri in 1993 indicated that the factor of needs among students is nearly decisive in shaping an individual’s personality and achieving psychological satisfaction. 3-The achievement motive is a significant factor in enhancing the psychological satisfaction of students, as demonstrated by Bales’ study.